Mapping and performance evaluation of mathematics education research in Turkey: A bibliometric analysis from 2005 to 2021 - Ercan Dede; Ercan Ozdemir (Journal of Pedagogical Research, 2022)
Different types of in-depth literature reviews were conducted to identify, evaluate or summarize the findings, common themes, trends, gaps, and used methods in mathematics education research. In recent decades, technological advances have enabled us to evaluate mathematics education literature in a more reliable, powerful, and objective manner. This study aims to present a complete description of Turkey-addressed mathematics education research using bibliometric methods. In other words, the current study aims to identify the most influential and/or productive authors, institutions, and publications in the field of mathematics education in Turkey. This study also aims to visualize and uncover the dynamic of the conceptual and intellectual structure of the field.  For this purpose, citation analysis, co-occurrence analysis, co-citation analysis, and science mapping were performed using 416 highly-qualified and SSCI-indexed articles obtained from the WoS database. The results of citation analysis indicate the most influential authors are A. Baki, B. Guven, and D. Akyuz, respectively while the most productive ones are M. Isıksal-Bostan, A. Kursat Erbas, and O. Birgin. The most effective and leading institutions in the field are METU, Karadeniz Technical, and Hacettepe Universities. Additionally, co-occurrence analysis indicates mathematical achievement, mathematical modelling, and attitude are the most commonly used author keywords. Co-citation mapping visualizes the knowledge base of the mathematics education research and uncover which subjects the scholars in the field benefited from the research studies of seminal authors. Based on the findings, the current study makes suggestions for the research topics that could be influential and needed further research in the field.